2017
DOI: 10.3847/2041-8213/aa94c6
|View full text |Cite
|
Sign up to set email alerts
|

Different Types of Ion Populations Upstream of the 2013 October 8 Interplanetary Shock

Abstract: We show for the first time that different types of suprathermal ion distributions may exist upstream of a single interplanetary shock. ACE and the two ARTEMIS satellites observed a shock on 8 October 2013. The ARTEMIS P1 and P2 spacecraft first observed field-aligned ions (P1) and gyrating ions (P2) arriving from the shock. These were followed by intermediate ions and later by a diffuse population. At the location of the P2 the shock exhibited an Alfvénic Mach number of M A =5.7 and was marginally quasi-perpen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 51 publications
1
15
0
Order By: Relevance
“…The ion foreshock observed by Cluster has complex ion distributions including beam and diffuse ions. This is in agreement with previous observations by Kajdič et al (2017) who described a variety of ion 10.1029/2019JA026748 distributions upstream of a single IP shock in the data of the ARTEMIS (Angelopoulos, 2011) spacecraft. These authors observed upstream ion distributions that changed from initial field-aligned (ARTEMIS-1) or gyrating (ARTEMIS-2) to intermediate and diffuse distributions.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The ion foreshock observed by Cluster has complex ion distributions including beam and diffuse ions. This is in agreement with previous observations by Kajdič et al (2017) who described a variety of ion 10.1029/2019JA026748 distributions upstream of a single IP shock in the data of the ARTEMIS (Angelopoulos, 2011) spacecraft. These authors observed upstream ion distributions that changed from initial field-aligned (ARTEMIS-1) or gyrating (ARTEMIS-2) to intermediate and diffuse distributions.…”
Section: Discussionsupporting
confidence: 93%
“…• Shock interaction with small flux ropes in the solar wind can change shock geometry and impact ion injection at the shock • Interplanetary shock interaction with flux ropes can modify the upstream and downstream regions • Fluxes of particles with energy up to 125 keV are affected by the FRLS-shock interaction, modulating associated ESP events and evolution of ion distributions upstream of an IP shock were discussed by Kajdič et al (2017). This study showed that different ion populations can be observed upstream of a single IP shock with M A ∼ 4.…”
Section: Key Pointsmentioning
confidence: 99%
See 1 more Smart Citation
“…Rippling was observed at the Earth's bow-shock by several authors by using multi-spacecraft data from Cluster [Horbury et al, 2002, 2001, Lobzin et al, 2008, Moullard et al, 2006 and Magnetospheric Multiscale (MMS) mission [Gingell et al, 2017, Johlander et al, 2016. As for the IP shocks, several authors [i.e., Kajdič et al, 2017, Koval & Szabo, 2010, Pulupa & Bale, 2008, Russell & Alexander, 1984, Russell et al, 2000, Szabo, 2005 discussed and/or observed their non-planar structure at scales of several tens of Earth radii (R E ), but never at ion scales.…”
Section: Introductionmentioning
confidence: 99%
“…Lario et al (2019) have described IP shock observations where enhancements in ions less than 10 keV appeared close to the shock. Similarly, ion populations of ~20 keV associated with an IP shock have been recorded by the ARTEMIS spacecraft (Kajdič et al 2017). In this paper we report experimental evidence of SDA in a population of 2-7 keV ions observed ahead of an interplanetary (IP) shock.…”
Section: Introductionmentioning
confidence: 64%